BEECH WOOD MODIFIED BY RADIO-FREQUENCY DISCHARGE PLASMA - Jurkovič, Peter; Sedliačik, Ján; Novák, Igor; Matyašovský, Ján; Chodák, Ivan; Kleinová, Angela (Innovation in Woodworking Industry and Engineering design, 2023)
The radio-frequency discharge plasma (RFDP) has been used to improve the wetting and adhesive properties of beech (Fagus Sylvatica L.) wood. The pre-treatment of wood surfaceusing discharge plasma is attractive for various wood applications, mainly because of its high efficiency and low production cost. Moreover, a significant increase of the polar component of wood surface energy after modification by RFDP has been identified, while the polar component of the surface energy is associated with the presence of acid-base forces (electron donor–acceptor bonds). The surface energy of beech wood pre-treated by RFDP during 120 s in air significantly decreased. The shear strength of adhesive joint beech wood-polyurethane adhesive increased non-linearly from 5.2 MPa (native beech wood) up to 7.8 MPa. FTIR-ATR results confirm the increase of the beech wood polarity during RFDP treatment due to growth in –OH polar groups amount. The enhancement of the wood wettability is a necessary condition to promote a better adhesion with a water-based adhesives and coatings, which is currently being studied.